Analisis Prilaku/Stabilitas Pendingin Thermoelektrik Yang Di Tenagai Matahari - Dwi Alia Widodo; Teuku Azuar Rizal; Nasruddin Abdullah (JURUTERA - Jurnal Umum Teknik Terapan, 2021)
Solar power is an environmentally friendly renewable energy source. Solar power is utilized by solar power plants to generate electricity. The electrical energy produced is light energy which is converted by solar cells. A collection of solar cells arranged in such a way as to produce solar panels. The electrical energy produced will be stored in a medium called a battery. In the storage and use of this electrical energy, care must be taken to avoid overcharging/overcharging and over-using/over-discharging. Therefore, a battery charge controller is used which will regulate charging or energy consumption, besides that it also functions as a protection device. For the use of AC loads, an inverter is used to adjust the output voltage to VAC.